Developing an Experience Documentation Model of Spiritual Health in the COVID-19 Epidemic (Journal of Pharmaceutical Negative Results, 2022)
Background & objective: Experience documentation is an important component of knowledge management. Experience documentation aims to elicit tacit knowledge of individuals, document its teachings, and make them publishable. This research develops and proposes a model for recording organizational experiences.Method: This research is a descriptive study that was performed qualitatively and quantitatively. The statistical population consisted of 24 people selected from academic experts, administrators, and executive experts using the snowball sampling method. Data were analyzed using SPSS and MaxQDA software. After studying the scientific documents and upstream documents, the effective components in experience documentation were extracted. Then, the questions related to each component were determined and validated during meetings with experts.Results: In this model, important events were first identified and the issues, measures, and decisions were then extracted. Finally, the suggestions, scenario planning and modeling, and teachings were identified.Conclusion: effective components in recording experiences and related questions can propose a good model for documenting organizational experiences. The results of this research can be used as a basis for managers to plan and implement experience documentation in their organizations.